PERBANDINGAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DAN GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA DI KELASVIII MTs. PP. HASANATUL BAROKAH TAHUN PEMBELAJARAN 2014/2015 - Ramadani, Epi; Afifah, Nurul; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of this research is to know comparation the result of student Learning IPA by using Cooperatif Learning , type Numbered Head Together (NHT) and Group Investigation (GI) methods. Research was carried out in MTs. PP. Hasanatul Barokah, on Desember 2014. Focusing on quaition experiment methods, with Two Group. Sample was collected purposive from 38 student divided into 2 classes, class NHT and GI. The Instrument used in this research is a multiple choice questions test and as a test instrument. The conclusion from the research was done there is an t0 3.928 Ë ttable 2.042. Is shows the differences in student learning IPA using cooperative learning methods of NHT and GI type.